A novel mineralized high strength hydrogel for enhancing cell adhesion and promoting skull bone regeneration in situ. (15th September 2020) - Zhang, Xintao; He, Yongyi; Huang, Pengzhou; Jiang, Guanwei; Zhang, Mengdi; Yu, Fei; Zhang, Wentao; Fu, Guo; Wang, Yao; Li, Wenqiang; Zeng, Hui
Abstract: Bone defect therapy based on advanced biocomposite hydrogel scaffolds provide a promising strategy in bone tissue engineering. Inducing bone regeneration that meets the biomechanical, bioactivity and osteoconductivity criteria of bone tissue engineering is highly appealing but challenging. Here, we designed a mineralized, high-strength and tough nanocomposite hydrogel by in situ deposition of calcium phosphate hydroxide salt nanohydroxyapatite (HAP) after photopolymerization of gelatin methacryloyl (GelMA), quaternized chitosan (QCS) and functional polyhedral oligomeric silsesquioxane (POSS), in which the POSS nanoparticles served as a physical-chemical crosslinker to reinforce the hydrogel network structure and improved mineralized capacity by silicon in POSS nanoparticle bonding to calcium ions. The fabricated nanocomposite hydrogels have excellent mechanical properties (tensile strength of 328.6 ± 14.3 kPa and compressive strength of 1.71 ± 0.24 MPa) and high cytocompatibility, significantly facilitated cell adhesion and upregulated osteodifferentiation. After treatment of a rat skull defect model for 12 weeks, the scaffold of the biomineralized hydrogel remarkably promoted new bone formation and accelerated bone regeneration in situ, suggesting its used as a promising substitute in bone tissue engineering.